In vitro evaluation of the effect of monobond etch and prime mep application on shear bond strength and bonding between resin cement and lithium disilicate glass ceramic - Meghlaj, Mustafa (My University, 2019)
Amaç: Bu çalışmanın amacı MEP uygulamasının rezin siman ve lityum disilikatseramik arasındaki makaslama bağlanma dayanımı üzerine etkisinindeğerlendirilmesidir.Gereç ve Yöntemler: Altmış adet ısıyla preslenmiş lityum disilikat diskler 2 grubaayrıldı (n = 15) (IPS E-max Pres ve GC LiSi Pres). İki grubun yuzeyıne 4.5% HF asiduygulandı ve 7 mm Kompozit Çubuk Tetric N-Ceram ve G-ænial posterior (VariolinkEsthetic LC ve G-CEM LinkForce DC) ile kaplandı. Diğer iki gruba ise MEP uygulandıve aynı yapıştırma simanı kullanıldı. Polimerizasyon için ve LED cihaz 1200 mW / cm2 kullanıldı. Sonrasında 5 ° C ve 55 ° C sıcaklıklarda 20000 termal döngü yapıldı.Kırılma dayanımı değerleri universal test cihazı (shimadzu universal machine) ileölçüldü. Verilerin istatistiksel analizi SPSS istatistik kullanılarak yapıldı.Ölçüm sonuçlarından elde edilen değişim değerlerinin istatistiksel olarakdeğerlendirilmesinde ANOVA testi kullanıldı. (P <0.05).Bulgular: Seramiklerin bağlama kuvveti üzerindeki etkisi istatistiksel olarak anlamlıbulunmadı (p = 0.699). SBS gösterdi, HF asidi ve GC siman en yüksek değeri 315,15± 90,6, ardından sırası ile variolink siman ile MEP 292,55 ± 84,38, variolink siman ileHF asidi, 274,06 ± 61,59 olduğu görüldü. MEP ve GC siman en düşük değeri (235,49± 79,3) göstermiştir.Sonuç: HF asitli GC siman tüm gruplar arasında en iyi sonucu göstermiştir. Variolinksiman bulunan MEP sistemi, diğer gruplarla kıyaslayınca daha iyi sonuçlargöstermiştir. Simantasyon işlemlerinde MEP intraoral olarak basit ve güvenli birşekilde kulanılabilir.

Aim: This study aims to evaluate the effect of monobond etch and prime (MEP)application on shear bond strength between resin cement and ceramics.Materials and Methods: Sixty heat-pressed lithium disilicate discs were divided intofour groups (n=15) (IPS E-max Press and GC Initial LiSi Press). Two groups werefabricated and surface treated by HF acid 4.5% and cemented to 7 mm diameterComposite bars of Tetric N-Ceram and G‐ænial posterior by (Variolink Esthetic LCand G-CEM LinkForce DC). The other two groups were treated by MEP and carriedout with the same cement sequence. LED device 1200 mW/ cm2 used for the curing andthermocycling procedure was carried out in 5°C and 55°C temperatures for 20000thermal cycles. Shear bond strength values were measured by a universal testingmachine (shimadzu universal machine). Statistical analysis of the data was performedusing the SPSS statistical program. ANOVA test will be used for statistical evaluationof the change values obtained from the measurement results (P <0.05).Results: The effect of ceramic on the binding force was not statistically significant(p=0.699). SBS showed, HF acid and GC cement yielded the highest value of 315,15 ±90,6, then MEP with variolink cement yielded 292,55 ± 84,38, HF acid with variolinkcement yielded 274,06 ± 61,59 and MEP with GC cement presented the lowest valueof 235,49 ± 79,3.Conclusion: GC cement with HF acid significantly showed the best result among allgroups. MEP system with variolink cement showed more desirable results incomparison to the remaining groups. Cementation steps can be done simply and safelyintraorally with MEP.
Keywords: cementation; Dental Prosthesis; Diş; Diş Protezleri; Health; makaslama bağlanma dayanımı; MEP; Sağlık; Shear bond strength; simantasyon MEP; Tooth